PENGARUH URUTAN OVULASI TERHADAP DAYA TETAS OVUM AYAM KAMPUNG (Gallus sp.) - Siti Roudlotul Hikamah (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2014)
Limitations of ayam kampung stock Gallus sp. in the market is one of the common causes of the farmers failed to hatch. This study aims to provide information to the farmers Gallus sp. about the effect of the order of ovulation to hatching ova ayam kampung (Gallus sp.). type of true experimental research, because all the variables are controlled. Technique of random sampling or simple random sampling. From the research that has concluded that Ovum high hatchability is before ovulation ovulation until the last second, next is the beginning of ovulation and the next order is final ovulation While tetasnya low power ovum is ova aftershocks.